Evaluasi Tingkat Kredit Macet Pembiayaan Syariah Terhadap Nasabah di Kota Sorong: Studi kasus PT BFI Finance Indonesia – Unit Usaha Syariah - Nihayatun Nuama; St. Umrah; Karfin Karfin (Prodi Ekonomi Syariah IAIN Sorong, 2022)
In maintaining credit problems that arise, it is carried out by carrying out SOPs in accordance with company regulations including financing analysis, handling accounts receivable (receivables), monitoring arrears to Non-Performing Financing (NPF) and solutions in reducing financing problems (bad credit). In this study, the authors discuss the problems, namely the level of bad loans in the form of credit quality in late payment of installment obligations to financing performance assessments in the form of NPF, handling finance companies on the quality of credit given to debtors related to Islamic financing. It can be seen that the level of non-performing financing (bad loans in the category of non-performing financing is quite high and quite high risk with a value above 5%). The need to re-conduct some considerations in the development of financing for four-wheeled vehicles (cars) in sharia financing, the use of Murabahah contracts and recommendations for implementation without late fees for customers who are in arrears until final handling with POJK Number 10/POJK.05/2019 concerning the implementation of finance company business sharia and sharia business units of finance companies and DSN Fatwa Number 111/DSN-MUI/IX/2017 concerning murabahah contracts.